PENGARUH PERPUTARAN PIUTANG USAHA DAN PENERAPAN PERATURAN PEMERINTAH (PP) NOMOR 23 TAHUN 2018 TERHADAP LABA SETELAH PAJAK PADA CV CIPTA BUKIT MAS PULOGADUNG - Fauziyah, Zakin Fauziyah; Bambang Santosa, Bambang Santosa; Adam, Adam (Cakrawala Akuntansi & Manajemen, 2024)
The main goal of a company is to achieve maximum profit in running its business. For companies, profit is very important to measure the ability and effectiveness of the company in managing its resources. There are several things that can affect profits, both internal and external factors, such as Accounts Receivable Turnover and the Implementation of Government Regulation Number 23 of 2018. The rise of MSMEs lately, sometimes pays little attention to this, for that good management is needed to achieve maximum profit. This study has a problem formulation of how much influence the Accounts Receivable Turnover and the Implementation of Government Regulation Number 23 Year 2018 on Profit After Tax at CV Cipta Bukit Mas Pulogadung partially and simultaneously. The purpose of this study was to determine the effect of Accounts Receivable Turnover and the Application of Government Regulation Number 23 of 2018 on Profit After Tax at CV Cipta Bukit Mas Pulogadung. The method used in this study is a verification method with a quantitative approach. The data used is secondary data from the 2018 and 2019 CV Cipta Bukit Mas Financial Statements obtained from direct observations in the field. The results of this study indicate that the independent variable that has a significant influence is the variable Application of Government Regulation Number 23 of 2018. The value of Profit After Tax will be better if it is influenced by Accounts Receivable Turnover and the Application of Government Regulation Number 23 of 2018 simultaneous